High prevalence of vitamin D insufficiency and its association with obesity and metabolic syndrome among Malay adults in Kuala Lumpur, Malaysia - Bulgiba Awang; Moy Foong-Ming (BMC, 2011)
Abstract Background Vitamin D status, as indicated by 25-hydroxyvitamin D is inversely associated with adiposity, glucose homeostasis, lipid profiles, and blood pressure along with its classic role in calcium homeostasis and bone metabolism. It is also shown to be inversely associated with metabolic syndrome and cardiovascular diseases in western populations. However, evidence from the Asian population is limited. Therefore, we aim to study the prevalence of vitamin D insufficiency (< 50 nmol/L) and the association of 25-hydroxyvitamin D with metabolic risk factors among an existing Malay cohort in Kuala Lumpur. Methods This is an analytical cross sectional study. A total of 380 subjects were sampled and their vitamins D status (25-hydroxyvitamin D), fasting blood glucose, full lipid profile were assessed using venous blood. Systolic and diastolic blood pressure, weight, height and waist circumference were measured following standard protocols. Socio-demographic data such as sex, age, smoking status etc were also collected. Data was analysed using t-test, chi-square test, General Linear Model and multiple logistic regression. Results Females made up 58% of the sample. The mean age of respondents was 48.5 (SD 5.2) years. Females had significantly lower mean Vitamin D levels (36.2; 95% CI: 34.5, 38.0 nmol/L) compared to males (56.2; 95% CI: 53.2, 59.2 nmol/L). Approximately 41% and 87% of males and females respectively had insufficient (< 50 nmol/L) levels of 25-hydroxyvitamin D (p < 0.001). The prevalence of Metabolic Syndrome for the whole sample was 38.4 (95% CI: 33.5, 43.3)%. In the multivariate model (adjusted for age, sex, abdominal obesity, HDL-cholesterol, diastolic blood pressure), insufficient Vitamin D status was significantly associated with 1-year age increments (OR: 0.93; 95% CI: 0.88, 0.98), being female (OR: 8.68; 95% CI: 5.08, 14.83) and abdominal obesity (OR: 2.57; 95% CI: 1.51, 4.39). Respondents with insufficient vitamin D were found to have higher odds of having Metabolic Syndrome (OR: 1.73; 95% CI: 1.02, 2.92) after adjusting for age and sex. Conclusions Our results highlight the high prevalence of vitamin D insufficiency among Malay adults in Kuala Lumpur. Vitamin D insufficiency is independently associated with younger age, female sex and greater abdominal obesity. Vitamin D insufficiency is also associated with Metabolic Syndrome.